A qualitative exploration of trial-related terminology in a study involving Deaf British Sign Language users - Young, Alys; Oram, Rosemary; Dodds, Claire; Nassimi-Green, Catherine; Belk, Rachel; Rogers, Katherine; Davies, Linda; Lovell, Karina (Current controlled trials in cardiovascular medicine, 2016)
Internationally, few clinical trials have involved Deaf people who use a signed language and none have involved BSL (British Sign Language) users. Appropriate terminology in BSL for key concepts in clinical trials that are relevant to recruitment and participant information materials, to support informed consent, do not exist. Barriers to conceptual understanding of trial participation and sources of misunderstanding relevant to the Deaf community are undocumented. A qualitative, community participatory exploration of trial terminology including conceptual understanding of 'randomisation', 'trial', 'informed choice' and 'consent' was facilitated in BSL involving 19 participants in five focus groups. Data were video-recorded and analysed in source language (BSL) using a phenomenological approach. Six necessary conditions for developing trial information to support comprehension were identified. These included: developing appropriate expressions and terminology from a community basis, rather than testing out previously derived translations from a different language; paying attention to language-specific features which support best means of expression (in the case of BSL expectations of specificity, verb directionality, handshape); bilingual influences on comprehension; deliberate orientation of information to avoid misunderstanding not just to promote accessibility; sensitivity to barriers to discussion about intelligibility of information that are cultural and social in origin, rather than linguistic; the importance of using contemporary language-in-use, rather than jargon-free or plain language, to support meaningful understanding. The study reinforces the ethical imperative to ensure trial participants who are Deaf are provided with optimum resources to understand the implications of participation and to make an informed choice. Results are relevant to the development of trial information in other signed languages as well as in spoken/written languages when participants' language use is different from the dominant language of the country.